A Study of the mechanical properties of aluminum composite materials prepared by atomization process - Jaffer, Harith Ibrahim (Iraqi Journal of Physics, 2011)
Steel fiber aluminum matrix composites were prepared by atomization technique. Different air atomization conditions were considered; which were atomization pressure and distance between sample and nozzle. Tensile stress properties were studied. XRF and XRD techniques were used to study the primary compositions and the structure of the raw materials and the atomized products. The tensile results showed that the best reported tensile strength observed for an atomization pressure equal to 4 mbar and sample to nozzle distance equal to 12 cm. Young modulus results showed that the best result occurred with an air atomization pressure equal to 8 mbar and sample to nozzle distance equal to 16cm